Adobe InDesign CC learn by video - Chelius, Chad.; Safari eBooks ([S.l.] : Peachpit Press, 2013)
"This critically-acclaimed interactive training program from Adobe Press offers exceptional quality high-definition video to teach the fundamentals of Adobe Indesign CC. Including more than 8 hours of video tutorials, the course comes complete with lesson files, assessment quizzes, and review materials. Experienced instructor Chad Chelius presents a comprehensive introduction to InDesign, including best practices as well as fundamental layout and document styling concepts. Topics covered include working with text, styles, and objects, and outputting files as ePubs, and how to work within the Creative Cloud. The video is wrapped in a unique interface that allows you to jump to any topic and also bookmark individual sections for later review. The unique 'Watch and Work' mode shrinks the video into a small window to allow you to work alongside in InDesign. Project files used in the lessons are included on the disc so you can practice what you've learned, and interactive review questions help reinforce freshly gained knowledge."--Resource description page.
Title from resource description page (viewed August 22, 2013).
Presenter, Chad Chelius.
Keywords: Adobe InDesign (Electronic resource); Desktop publishing; Electronic books